Care or custody? - Laing, Judith M. (Oxford University Press, 1999)
This book is a comprehensive account of how mentally disordered offenders are treated when they come into contact with the criminal justice system. It traces the historical developments and analyzes the existing mental health and criminal provisions. It includes a theoretical overview of the law and an analysis of some of the theoretical issues surrounding the treatment and detention of mentally disordered offenders